2004
DOI: 10.1117/12.528546
|View full text |Cite
|
Sign up to set email alerts
|

The formation of GaAs/Si photodiodes by pulsed-laser deposition

Abstract: Hetero-pairing of thin-film GaAs on Si is of considerable interest for novel applications in optoelectronics. However, the formation of high-quality GaAs is difficult and requires expensive top technologies such as molecular beam epitaxy (MBE) and related methods. In general, MBE forms high-quality epitaxial layers but is not capable of the straightforward formation of GaAs on Si because of the 4.1% lattice mismatch between both materials. We have developed and explored the possibilities of pulsed-laser deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Apparently, ultraviolet PLD causes a different GaAs/Si interface morphology than the other two employed laser lines. We already speculated in a previous work that the interface morphology depends on the PLD line employed [9]. Concerning hetero-device engineering, this work introduces PLD as an undemanding versatile method to form GaAson-Si devices for optoelectronic applications.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Apparently, ultraviolet PLD causes a different GaAs/Si interface morphology than the other two employed laser lines. We already speculated in a previous work that the interface morphology depends on the PLD line employed [9]. Concerning hetero-device engineering, this work introduces PLD as an undemanding versatile method to form GaAson-Si devices for optoelectronic applications.…”
Section: Discussionmentioning
confidence: 85%
“…Although first attempts already took place in the 1980s [5], the formation of GaAs-on-Si with PLD is, in comparison with MBE and MOCVD, considerably lesser exploited and almost no data were available when we started our activities. Meanwhile, we have demonstrated that nanosecond PLD forms photosensitive thin-film GaAs on glass and Si [6][7][8][9] and that the films can be used for novel all-optical logic operations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only one paper [5] containing data on GaAs-on-Si PLD before we started to work on the subject four years ago. Meanwhile, we demonstrated that PLD of p-type GaAs onto counter-doped Si produces a technologically appealing photo-responsive hetero-pair with sensitive bias dependence [6][7][8][9]. In the current work, we emphasize the dynamic rectification properties and the doping features of p-GaAs/n-Si structures formed with PLD at 355, 532, and 1064 nm.…”
mentioning
confidence: 70%
“…The flux and ablation time combinations resulted in film thicknesses of 300 nm, 600 nm, and 180 nm, for the ablation at 355 nm, 532 nm, and 1064 nm, respectively. The electric contacts have been realized in the same way as in [6][7][8][9], i.e., with vacuum evaporated Al on the GaAs layer and with sliver paste to the substrate. The dynamic rectification capabilities of the samples were checked with alternating current (AC) measurements at room temperature without illumination.…”
mentioning
confidence: 99%
“…This clearly established orientation opens the possibility to lower the costs for certain MBE and MOCVD based processes by using PLD GaAs on glass as wafer material instead of bulk material. Meanwhile, Raman investigations of the film surface have shown that the films consist of microcrystallites embedded in a predominantly amorphous texture [16]. Since the crystals are spread out uniformly over the film surface, the x-ray picks up their (111) orientation.…”
mentioning
confidence: 99%